Penerapan Grafik Pengendali DOB (Decision On Belief) Untuk Pengendalian Kualitas Produksi Air Mineral Dalam Kemasan (AMDK) - Auliya, Fitrotul; Rozi, Fachrur (Jurnal Riset Mahasiswa Matematika, 2024)
Efforts to maintain or control the quality of a process are the goals of quality control. One of the tools used is the control chart. A control chart is a graph that shows whether a process is in a controlled state or not. Decision On Belief (DOB) is a new method used to detect defects in a product. The DOB control chart has been proven to be more sensitive in detecting out-of-control data compared to other charts. Data will be analyzed using bar charts, Pareto diagrams, and cause-and-effect diagrams, followed by a distribution test, which shows that the data follows a Poisson distribution. This study applies the DOB chart using two phases: Phase I is used to determine the control limits. In Phase I, the control limits are obtained with values of =49,11 and =7,008. The application of the DOB chart in Phase II shows that the production process is out of control based on the analysis of   = 1,2,...,20. The application of the DOB chart in bottled mineral water production is expected to assist in the control process and improve the quality of packaged mineral water in the future.